2016
DOI: 10.1104/pp.16.01106
|View full text |Cite
|
Sign up to set email alerts
|

An Oxalyl-CoA Synthetase Is Involved in Oxalate Degradation and Aluminum Tolerance

Abstract: Acyl Activating Enzyme3 (AAE3) was identified to be involved in the catabolism of oxalate, which is critical for seed development and defense against fungal pathogens. However, the role of AAE3 protein in abiotic stress responses is unknown. Here, we investigated the role of rice bean (Vigna umbellata) VuAAE3 in Al tolerance. Recombinant VuAAE3 protein has specific activity against oxalate, with K m = 121 6 8.2 mM and V max of 7.7 6 0.88 mmol min 21 mg 21 protein, indicating it functions as an oxalyl-CoA synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(77 citation statements)
references
References 52 publications
8
69
0
Order By: Relevance
“…; Lou et al . ). In certain other oxalate‐degrading microbes, oxalyl‐CoA could be reduced back to glyoxylate, where a glyoxylate dehydrogenase is responsible for the catalysis.…”
Section: Discussionmentioning
confidence: 97%
“…; Lou et al . ). In certain other oxalate‐degrading microbes, oxalyl‐CoA could be reduced back to glyoxylate, where a glyoxylate dehydrogenase is responsible for the catalysis.…”
Section: Discussionmentioning
confidence: 97%
“…14 To date, AAE3 proteins from rice bean, Medicago truncatula, and Arabidopsis (Arabidopsis thaliana) have been characterized as oxalyl-CoA synthetases. 13,15,16 Here, amino acid sequence alignment revealed that AAE3 proteins from common buckwheat and amaranth display high identity with known AAE3 proteins, all having a conserved AMP binding domain and acetylCoA synthetase domain (Fig. 2).…”
mentioning
confidence: 84%
“…However, we previously demonstrated that oxalate accumulation is harmful for root growth in response to Al stress in rice bean (Vigna umbellata). 13 We further identified a gene VuAAE3 (Vigna umbellata Acyl Activating Enzyme3) that converts oxalate to oxalyl-CoA, thereby preventing oxalate toxicity induced by Al stress. 13 Although in silico analysis revealed that AAE3 proteins seem to be conserved among plant species, more evidence is required to support the viewpoint that AAE3 proteins-dependent Al resistance mechanism is conserved among plant species.…”
mentioning
confidence: 99%
See 2 more Smart Citations